Risk analysis for post-surgical complications in tuberculosis spondylitis patients with concurrent HIV infection - E. V. Reshetneva; A. Yu. Mushkin; V. N. Zimina (Туберкулез и болезни лёгких)
The article presents the analysis of immediate and postponed outcomes of surgical treatment of tuberculosis spondylitis in HIV-infected patients; the relative risks of post-surgery complications have been estimated.